[OP.3B.06] WILL BE CENTENARIANS, HYPERTENSIVE INDIVIDUALS? HOW IS THE BLOOD PRESSURE CONTROL OF CENTENARIANS IN PORTUGAL?. (September 2016) - Silva, A. Pereira Da; Matos, A.; Ribeiro, R.; Gil, A.; Clara, J. Gorjão; Bicho, M. Pires
Abstract : Objective: To assess blood pressure (BP) levels and the prevalence of hypertension (HBP) and its control in individuals centenarians in Portugal. Design and method: The study comprised a Caucasian population of 253 centenarians (77.9% women), with a mean age of 100.3 ± 2.0 years old, from different regions of Portugal. It were hypertension criteria those of ESH/ESC 2013 and or under anti hypertensive medication. Controlled BP values were considered according to JNC8. For the blood pressure measurements a Colson MAM BP3AA1–2 device was used. The mean arterial pressure, pulse pressure and the myocardial volume oxygen consumption (MVOC), were calculated. Results: The mean values for BP were: systolic (SBP) 134.14 ± 20.91 mmHg and diastolic (DBP) 68.48 ± 11.66 (range 80–199 mmHg for systolic and 55–114 mmHg for diastolic respectively), mean arterial pressure of 90.37 ± 12.81, range 60.67–126.0 and pulse pressure (PP) of 65.66 ± 18.02, range 14–116 mmHg. The average cardiac frequency was 74.49 ± 11.56 range 43–110 and of MVOC it was 99.68 x10–2 ± 20.71 x10–2 range 49x10–2–163.8x10–2 There were no significant differences in any of the above parameters, between genders. According to hypertensive criteria, 62.8% of the centenarian's individuals were hypertensive. From overall sample individuals, 58.1% presented blood pressure levels within the normal range, and the others, HBP, being 27.3% grade 1, 12.6% grade 2 and 2% grade 3. There were no significant differences in the distribution of levels of hypertension among genres. From the sample, 36.8% of subjects had isolated systolic hypertension. The hypertensive patients were mainly treated with: diuretics (43.1%), ACE inhibitors (18.5%), angiotensin receptor blockers, (15.5%), calcium channel blockers (8.6%), beta blockers (6.9%). Considering the pharmacological control of hypertensive subjects only 23.3% had SBP and 5.1% DBP uncontrolled, respectively 25.4% and 5.6% of women and 16.1% and 3.6% of men (p > 0.05). Conclusions: Hypertension exists between the centenarians individuals, but for the most part is of mild degree and is controlled, with no apparent differences between genders.